Investigation on serum Ca and P levels in cows with retained placenta - Öcal, H; Türköz, Y; Çetin, H; Kaygusuzoglu, E; Risvanli, A; Kalkan, C (Scientific Technical Research Council Turkey, 1999)
This study was carried out to investigate serum Ca and P levels in 31 cows with retained placenta (RP) and 8 cows without RP (control group). The RP was observed following normal parturition in 21 cows (RPP), and the remaining 10 cows had RP after abortion (RPA). Serum Ca and P levels did not differ significantly between the cows with RP and the control group (p>0.05). When the cows with RP were subdivided into two groups as the cows with RPP and those with RPA; the difference in the levels of P between these groups and the control group was not significant (p>0.05). However, the average Ca level of the cows with RPP was significantly lower than that of the cows with RPA and the control group (p<0.05). There was an association between the sex of calf and serum Ca level in the cows with RP. The Ca level of the cows which had female carves was significantly lower than that of cows which had male calves (p<0.05). When the seasonal distribution of RP was considered, there was no significant difference between seasons in terms of Ca levels (p>0.05), whereas P levels of cows with RP (n=6) occured in spring were significantly lower than those of cows with RP (n=15) occured in summer (p<0.01).
Retensiyo Sekundinarumlu İneklerde Kan Serumu Kalsiyum (Ca) ve Fosfor (P) Düzeyleri Üzerine Çalişma
Keywords: retained placenta; serum; Ca; P; cow